Elucidating afferent-driven presynaptic inhibition of primary afferent input to spinal laminae I and X - Krotov, Volodymyr; Agashkov, Kirill; Romanenko, Sergii; Halaidych, Oleh; Andrianov, Yaroslav; Safronov, Boris V.; Belan, Pavel; Voitenko, Nana (Frontiers in Cellular Neuroscience, 2023)
Despite the fact that spinal processing of nociceptive information greatly relies on afferent-driven presynaptic inhibition (PI), the pattern of its induction in different types of primary afferents is poorly understood. The lack of knowledge can be explained, at least in part, by technical challenges in examining this complex phenomenon. Here we examined the primary afferent-driven PI of fibers supplying neurons in spinal laminae I and X. Unmyelinated C-fibers were selectively activated by electrical stimuli of negative polarity that induced anodal block of myelinated A-fibers. Combining this approach with patch clamp recordings in ex-vivo spinal cord preparations, we could directly study PI in second order sensory neurons. We found that attenuation of the A-fiber-driven PI resulted in appearance of new mono- and polysynaptic C-fiber-mediated EPSC components. Such homosegmental A-fiber-driven PI was observed for the neurons located in the segment of the dorsal root entrance as well as for the neurons in the adjacent rostral segment. In their turn, C-fibers from the L5 dorsal root induced heterosegmental PI of inputs from the L4 Aδ- and C-afferents to the neurons in L4 segment. Heterosegmental C-fiber-driven PI was reciprocal: the L4 C-fibers inhibited the L5 Aδ- and C-fiber inputs and even weakly affected the direct L5 Aβ-fiber input to lamina I neurons. Moreover, C-fiber-driven PI was found to control spike discharges. Given that homosegmental A- and heterosegmental C-fiber-driven PI affected substantial proportion of lamina I and X neurons, we suggest that these basic mechanisms are crucially important for the input control in the spinal nociceptive-processing network.